Quality Of Nursing Work Life Improvement Model to Decrease Nurse Intention to Quit in Premier Surabaya Hospital - Jany Prihastuty; Nyoman Anita Damayanti; Nursalam Nursalam (Universitas Airlangga, 2013)
Introduction: Quality of Nursing Work Life (QNWL) is a thing that needs attention by human resource management approach. The purpose of this research was to provide develop model to increase QNWL in order to lower nurse’s intention to quit the Premier Hospital Surabaya.Methods: Design used in the structure was explanatory research. The independent variables was Internal factors (Individual factors, social and environment conceptual factors, operational factors, administrative factors) where as the dependent variable from this study was intention to quit, and moderator variables QNWL random sampling technique. Total sample was 160 nurses, taken according to inclusion criteria. The research was conducted in Premier Hospital Surabaya from October 2012 - July 2013. Data were collected by using structured questionnaire. Data were then analyzed by using multiple linear regression test with level of significance of ≤ 0.05. Result: The results showed, QNWL was influenced by relationships inter-professional part of variabel social and environment conceptual factors, supervision monitoring part of variabel operational factors, career development part of variabel administrative factors. Intention to quit influenced by relationships between nurses, inter-departmental and inter-professional part of variabel social and environment conceptual factors and salaries and benefits part of variabel administrative factors with significant value p = 0.005.Discussion: It can be concluded good inter-professional relation, supervision monitoring, and good career development affected QNWL. Good relationships between nurses, inter-departmental and inter- professional led to lower intention to quit. Low salary and benefits led nurse’s intention to quit getting stronger.